Tools and weapons : the promise and the peril of the digital age - Smith, Brad (Brad Lee), 1959-; Browne, Carol Ann (Penguin Press, 2019)
"In Tools and Weapons, Brad Smith and Carol Ann Browne take us into the cockpit of one of the world's largest and most powerful tech companies as it finds itself in the middle of some of the thorniest emerging issues of our time. These are challenges that come with no preexisting playbook, including privacy, cybercrime and cyberwar, social media, the moral conundrums of artificial intelligence, big tech's relationship to inequality, and the challenges for democracy, far and near. While in no way a self-glorifying "Microsoft memoir," the book pulls back the curtain remarkably wide onto some of the company's most crucial recent decision points, as it strives to protect the hopes technology offers against the very real threats it also presents. There are huge ramifications for communities and countries, and Brad Smith provides a thoughtful and urgent contribution to that effort"--